Optimal Simple Rules for Fiscal Policy in a Monetary Union - Lukas Vogel; Werner Roeger; Bernhard Herz (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
The paper discusses the stabilizing potential of fiscal policy in a dynamic general-equilibrium model of monetary union. We consider a small open economy inside the currency area. We analyze the demand and supply effects of direct taxation, indirect taxation and government spending and derive optimal simple rules for fiscal stabilization of a technology shock. Fiscal policy achieves substantial macroeconomic stabilization. Simple public-expenditure rules show the highest degree of both output and inflation stabilization. The implementation lag substantially weakens output stabilization, but hardly affects the stabilization of prices. Out-put-oriented rules imply less instrument inertia than inflation-dominated rules. The implemen-tation lag leads to higher coefficients for inflation relative to output in the optimal rule. Com-pared to the single-instrument approach the simultaneous optimization of two instrument rules implies only little additional stabilization gains.
Keywords: E37; E62; F41; 330; Fiscal policy; monetary union; simple policy rules